Persistent subretinal fluid due to central serous chorioretinopathy after retinal detachment surgery - Moreno-López M; Pérez-López M; Casas-Llera P; Jarrín E; Muñoz-Negrete FJ (Clinical Ophthalmology, 2011)
María Moreno-López, Marta Pérez-López, Pilar Casas-Llera, Elena Jarrín, Francisco José Muñoz-NegreteOphthalmology Unit, Hospital Ramón y Cajal, Madrid, SpainBackground: The causes of persistent submacular detachment after successful rhegmatogenous retinal detachment (RRD) surgery remain unknown. Its presence is associated with poor postoperative visual acuity, but due to its spontaneous resolution no additional therapeutic or diagnostic procedure is recommended.Case report: A case of central serous chorioretinopathy (CSC) that simulated persistent subfoveal fluid after RRD surgery is presented.Conclusion: To the authors' knowledge, no other case of visual impairment after successful retinal detachment surgery due to CSC has been reported in the PubMed database. In view of this report, CSC should be considered in the differential diagnosis of persistent subretinal fluid after successful retinal detachment surgery.Keywords: persistent subretinal fluid, retinal detachment surgery, central serous chorioretinopathy, vitrectomy